2015
DOI: 10.4172/2161-0509.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Mid Pregnancy Fetal Growth Restriction and Maternal Anaemia a Prospective Study

Abstract: Background: Fetal growth restriction (FGR) in anaemic women leads to high perinatal morbidity, mortality and long term sequelae too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…WHO has estimated that the prevalence of anemia in developed country is 14% and 51% in developing country. In India, WHO has estimated the prevalence of 65-75% [3] . National Family Health Survey (NFHS) -II in 1998-99 showed that 54% of women in rural and 46% women in urban are anaemic [4] .…”
Section: Introductionmentioning
confidence: 99%
“…WHO has estimated that the prevalence of anemia in developed country is 14% and 51% in developing country. In India, WHO has estimated the prevalence of 65-75% [3] . National Family Health Survey (NFHS) -II in 1998-99 showed that 54% of women in rural and 46% women in urban are anaemic [4] .…”
Section: Introductionmentioning
confidence: 99%